Experimental and computational study of the structural and electronic properties of Fe(II)(2,2'-bipyridine)(mes)2 and [Fe(II)(2,2'-bipyridine)(mes)2]-, a complex containing a 2,2'-bipyridyl radical anion. - Irwin, M; Jenkins, R; Denning, MS; Krämer, T; Grandjean, F; Long, G; Herchel, R; McGrady, J; Goicoechea, J (2010)
Addition of potassium metal and 2,2,2-crypt (4,7,13,16,21,24-hexaoxa-1,10-diazabicyclo[8.8.8]hexacosane) to a tetrahydrofuran (THF) solution of Fe(2,2'-bipyridine)(mes)(2) (1; mes = 2,4,6-Me(3)C(6)H(2)) yielded the anionic complex [Fe(2,2'-bipyridine)(mes)(2)](-) which was isolated as [K(2,2,2-crypt)][Fe(2,2'-bipyridine)(mes)(2)] (2) alongside the side-product [K(2,2,2-crypt)][Fe(mes)(3)] x C(6)H(12) (3). A compositionally pure sample of 2 was obtained by dissolving a mixture of 2 and 3 in dry pyridine and layering the resulting solution with toluene. Solid state magnetic susceptibility measurements on 1 reveal Curie-Weiss paramagnetic behavior with a molar magnetic moment of 5.12(1) mu(B) between 20 and 300 K, a value which is in line with the expected iron(II) spin-only value of 4.90 mu(B). The magnetic measurements carried out on 2 reveal more complex temperature dependent behavior consistent with intramolecular antiferromagnetic coupling (J = -46 cm(-1)) between the unpaired electrons of the iron(II) ion (S(Fe) = 2) and a pi* orbital of the bipyridyl radical (S(bipy) = 1/2). Structural data, Mossbauer and electron paramagnetic resonance (EPR) spectroscopic measurements, and density functional theory (DFT) calculations are all consistent with this model of the electronic structure. To the best of our knowledge, species 2 represents the first crystallographically characterized transition metal complex of the 2,2'-bipyridyl ligand for which magnetic, spectroscopic, and computational data indicate the presence of an unpaired electron in the pi* antibonding orbital.